The primary controlling parameters of porosity, permeability, and seepage capability of tight gas reservoirs: a case study on Upper Paleozoic Formation in the eastern Ordos Basin, Northern China - Hong-Jun Qu (KeAi Communications Co., Ltd., 2019)
Abstract Tight sandstone gas (hereafter “tight gas”) has become a subject of unconventional gas exploration globally. The large-scale development and use of tight gas resources in the USA, in particular, facilitated the rapid rebound of natural gas production in the USA, in addition to driving the rapid development of tight gas worldwide. In the eastern Ordos Basin, the Upper Paleozoic feature includes multiple layers of gas, a shallow depth, and notable potential for exploration and development. However, the reservoirs in the area are relatively tight, exhibit strong heterogeneity, and possess a complex micropore structure, thus restricting the effective economic development of oil and gas. Thus, research on the primary parameters controlling pore throat structure and the seepage capability of low-permeability reservoirs will be beneficial for the efficient exploration and development of natural gas in the eastern Ordos Basin. The parameters of reservoir porosity and percolation ability, as well as permeability, were analyzed using systematic sampling of the of the Upper Paleozoic Benxi, Taiyuan, and Shanxi Formations in the eastern Ordos Basin, constant-rate mercury injection experiments, nuclear magnetic resonance analysis, and gas–water-phase experimental studies. The results indicate that reservoir porosity is controlled by the effective pore volume and number, whereas permeability is controlled by the largest throat radius, rather than the average. The effective pore volume controls the movable fluid saturation, while reservoir percolation capability is controlled by the effective pore volume, irreducible water saturation, and size of the gas–water two-phase seepage zone.